Integration of knowledge discourse in Sri Lanka: Naleemiah Institute of Islamic Studies and its quest for Islamic religious education reform - Mohamed Zacky, Mohamed Fouz; Careem, Arafath (Centre for Islamisation (CENTRIS), IIUM, 2024)
The establishment of the Naleemiah Institute of Islamic Studies (1973) is seen as a crucial moment in the history of religious education for Muslims in Sri Lanka. The institution is committed to improving Islamic religious education by graduating students who are knowledgeable in both Islamic sciences and humanities. Given this background, this paper seeks to assess the institution's impact and effectiveness in promoting the integration of knowledge discourse in Sri Lanka. The findings suggest that the institution has succeeded in mainstreaming the basic idea of integration of knowledge and creating awareness about the importance of synthesizing Islamic studies, social sciences, and humanities into a unified framework over the five decades of its academic journey. However, this study finds that the institution has not yet systematized or conceptualized its integration model considering the contemporary debates about Islam and modern knowledge. As a result, this study recommends that NIIS refine its academic outlook and be involved in some intensive intellectual conversations about enhancing its academic commitment to the integration of knowledge framework and finding new modalities. Finally, this is a qualitative study that drew its data from both primary and secondary sources.